Teaching Grammar the Fun Way - Trajkova, Zorica (ELTAM, 2018)
Grammar seems to be the most difficult part of learning a language so creators of teaching materials must design grammar exercises which will make studying it more enjoyable and fun. This paper presents various techniques which can be employed by material designers to present grammar to students in the most acceptable manner so that they can adopt it easily. More precisely, it offers practical examples from the textbook aimed at teaching English for law enforcement students designed for students at the Faculty of Security in Macedonia. However, the paper offers advice on how these types of exercises can be adapted for teaching English to all levels and for all purposes.
Keywords: grammar, textbook for law enforcement, material design